College Students Social-Emotional Learning and Work Readiness Skills: Inputs for Internship Success - Alim, Kharim Angelo R. (International Journal of Research in Interdisciplinary Studies, 2026)
The transition from academic to the professional world poses significant challenges for students, necessitating the development of both technical and interpersonal competencies. This study investigates the relationship between Social-Emotional Learning (SEL) and Work Readiness Skills (WRS) among college students preparing for internships, using a descriptive-correlational design with regression analysis. Data were collected from 174 third-year students in a state university in Talakag, Bukidnon, Philippines, employing validated survey instruments adapted from established frameworks. Findings revealed that students generally demonstrated high levels of SEL and WRS, with SEL encompassing self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. A strong, positive, and highly significant relationship was identified between SEL and WRS. Regression analysis further confirmed SEL as a strong predictor of WRS. These results underscore the critical role of SEL in enhancing students’ employability by fostering both soft skills and job-specific competencies. Integrating SEL into academic programs can better prepare students for internship success and future employment. Recommendations include curriculum enhancement, faculty training on SEL facilitation, and student participation in SEL-focused activities to bridge the gap between academic learning and workforce demands.